Synthesis of chemically bonded porous ceramics from MgO–C refractory bricks waste. Issue 3 (1st February 2022) - Luza, A.L.; Simão, L.; Acordi, J.; Raupp-Pereira, F.; Innocentini, M.D.M.; Montedo, O.R.K.
Abstract: Chemically bonded ceramics (CBCs) obtained from industrial waste have attracted great interest in recent years. In the present work, MgO raw material was substituted with refractory MgO–C bricks waste (MgW) for CBCs. Monopotassium phosphate (KDP) and MgW were used as binder systems with varied component ratios (KDP/MgW) of 0.17–0.33 (mass basis) and waste (MgO–C) particles with D50 = 20.5 μm. Bodies containing K-struvite phase (MgKPO4 ·6H2 O), with compressive strength ranging from 1 to 1.4 MPa, were obtained. The total porosity ranged between 60 and 74%. Air permeability tests proved the presence of interconnected pores because the coefficients k1 and k2 increased with the increasing total porosity of the samples. The leaching test showed that the waste and the samples were nonreactive, nontoxic, and nonhazardous according to the Brazilian standard. The results showed that MgW-based chemically bonded porous ceramics can be produced from MgO–C refractory brick waste via synthesis processes for using as filters.